Fire severity effects on ash chemical composition and water-extractable elements - Pereira, Paulo; Úbeda, Xavier; Martin, Deborah A (Geoderma, 2012)
The effects of fire in the landscape are commonly assessed through the evaluation of ash properties. Among other properties, colour is one of the methods more frequently used. However, little is known about the effect of fire severity on ash chemical and extractable elements. Ash is an important source of nutrients in terms of landscape recovery after fire. In this study we analysed the effects of fire severity (estimated using ash colour) on ash chemical properties, CaCO3, pH, Total Carbon (TC), Total Nitrogen (TN), C/N ratio and some ash water-extractable elements, such as Calcium (Ca), Magnesium (Mg), Sodium (Na), Potassium (K), Total Phosphorous (TP), Total Sulphur (TS) and Silica (Si) collected in Portugal (N=102) after three wildfires that occurred in the same ecosystem, composed mainly of maritime pine, Pinus pinaster, and cork oak, Quercus suber. The results showed significant statistical differences among ash colour at a p<0.05 for ash water-extractable K and Si, at a p<0.01 for ash water-extractable Ca, Mg, Na and TS, and the major differences were observed (at a p<0.001) for ash CaCO3, pH, TC, TN, C/N ratio and water-extractable TP. Ash CaCO3, pH and water-extractable TS increased with fire severity and ash TC, TN, C/N ratio and water-extractable TP showed a decrease. In the remaining elements, no trend is identified. Major concentrations of ash TC, TN, C/N ratio and water-extractable Ca, Mg and K were identified in very dark brown and black ash. CaCO3, pH and water-extractable TS were identified in higher quantities in light grey ash. These findings show that fire severity is an important determinant of the type and amount of water-extractable nutrients present in ash that later can be incorporated into the soil and become available for plant growth.
Keywords: Ash chemical properties; Ash colour; Ash properties; fire severity; Landscape recovery; Water-extractable elements

A model for wildfire prevention planning in game resources - Zamora, R; Molina-Martínez, J R; Herrera, M.a.; Rodríguez y Silva, F (Ecological Modelling, 2010)
The high incidence of hunting activity and forest ﬁres in different ecosystems (particularly in Mediterranean ecosystems) requires a model, which allows for the comprehensive management of hunting resources and estimating the potential damage caused by this type of disturbance. This paper proposes a model for evaluating the socio-economic effects of forest ﬁres on hunting. Its cornerstone lies in evaluating hunting resource availability for each ecosystem within its territorial mosaic. Each game management unit (GMU) is identiﬁed by vegetation structure and habitat type. It presents a novel approach in which the economic value of each game management unit is linked to potential forest ﬁre damages. The effect a forest ﬁre has on an entire ecosystem depends on the intensity of its ﬂames. A sample study was undertaken in the province of Huelva in Andalusia (southern Spain). The socio-economic hunting vulnerability of the province of Huelva was 45,188,000D . The results obtained conﬁrmed the need for an economic appraisal of non-forest products in the forest and other woodland areas. Geographic Information System increases the ﬂexibility and simplicity of our methodology which permits immediate extrapolation to other agroforestry territories.
Keywords: fire severity; Fire-preventive planning; Hunting assessment; natural resources; Wildﬁre modeling

Influence of fire severity on plant regeneration by means of remote sensing imagery - Díaz-Delgado, R.; Lloret, F.; Pons, X. (International Journal of Remote Sensing, 2003)
In this paper we analyse the interactions between fire severity (plant damage) and plant regeneration after fire by means of remote sensing imagery and a field fire severity map. A severity map was constructed over a large fire (2692 ha) occurring in July 1994 in the Barcelona province (north-east of Spain). Seven severity classes were assigned to the apparent plant damage as a function of burning intensity. Several Landsat TM and MSS images from dates immediately before and after the fire were employed to monitor plant regeneration processes as well as to evaluate the relationship with fire severity observed in situ . Plant regeneration was monitored using NDVI measurements (average class values standardized with neighbour unburned control plots). Pre-fire NDVI measurements were extracted for every plant cover category (7), field fire severity class (7), and spatial cross-tabulation of both layers (33) and compared to post-fire values. NDVI decline due to fire was positively correlated with field fire severity class. Results show different patterns of recovery for each dominant species, severity class and combination of both factors. For all cases a significant negative correlation was found between damage and regeneration ability. This work leads to a better understanding of the influence of severity, a major fire regime parameter on plant regeneration, and may aid to manage restoration on areas burned under different fire severity levels.
doi: 10.1080/01431160210144732doi: 10.1080/01431160210144732The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: dominant species (voyant); fire severity; NDVI; plant damage; plant regeneration

Influence of fire severity on plant regeneration by means of remote sensing imagery - Díaz-Delgado, R; Lloret, F; Pons, X (International Journal of Remote Sensing, 2003)
In this paper we analyse the interactions between fire severity (plant damage) and plant regeneration after fire by means of remote sensing imagery and a field fire severity map. A severity map was constructed over a large fire (2692 ha) occurring in July 1994 in the Barcelona province (north-east of Spain). Seven severity classes were assigned to the apparent plant damage as a function of burning intensity. Several Landsat TM and MSS images from dates immediately before and after the fire were employed to monitor plant regeneration processes as well as to evaluate the relationship with fire severity observed in situ . Plant regeneration was monitored using NDVI measurements (average class values standardized with neighbour unburned control plots). Pre-fire NDVI measurements were extracted for every plant cover category (7), field fire severity class (7), and spatial cross-tabulation of both layers (33) and compared to post-fire values. NDVI decline due to fire was positively correlated with field fire severity class. Results show different patterns of recovery for each dominant species, severity class and combination of both factors. For all cases a significant negative correlation was found between damage and regeneration ability. This work leads to a better understanding of the influence of severity, a major fire regime parameter on plant regeneration, and may aid to manage restoration on areas burned under different fire severity levels.
doi: 10.1080/01431160210144732
Keywords: dominant species (voyant); fire severity; NDVI; plant damage; plant regeneration